Predictability alters multisensory responses by modulating unisensory inputs - Smyre, Scott A.; Bean, Naomi L.; Stein, Barry E.; Rowland, Benjamin A. (Frontiers in Neuroscience, 2023)
The multisensory (deep) layers of the superior colliculus (SC) play an important role in detecting, localizing, and guiding orientation responses to salient events in the environment. Essential to this role is the ability of SC neurons to enhance their responses to events detected by more than one sensory modality and to become desensitized (‘attenuated’ or ‘habituated’) or sensitized (‘potentiated’) to events that are predictable via modulatory dynamics. To identify the nature of these modulatory dynamics, we examined how the repetition of different sensory stimuli affected the unisensory and multisensory responses of neurons in the cat SC. Neurons were presented with 2HZ stimulus trains of three identical visual, auditory, or combined visual-auditory stimuli, followed by a fourth stimulus that was either the same or different (‘switch’). Modulatory dynamics proved to be sensory-specific: they did not transfer when the stimulus switched to another modality. However, they did transfer when switching from the visual-auditory stimulus train to either of its modality-specific component stimuli and vice versa. These observations suggest that predictions, in the form of modulatory dynamics induced by stimulus repetition, are independently sourced from and applied to the modality-specific inputs to the multisensory neuron. This falsifies several plausible mechanisms for these modulatory dynamics: they neither produce general changes in the neuron’s transform, nor are they dependent on the neuron’s output.